RANCANG BANGUN RASIO GEAR TERHADAP KECEPATAN PENGEROLAN PIPA (P3M Politeknik Negeri Cilacap, 2018)
The basic principle of metal formation is a process that is done by giving shape changes on the workpiece. This shape change can be done by providing an outer force resulting in plastic deformation. The application of this metal formation can be seen in some examples such as rolling, bending, forging, extruding, wire drawing, deep drawing, and so on. In the process of formation of this metal is also used tooling (bending) whose function gives style to the workpiece, and direct the change of shape. Knowing the speed of the power forwarding system on the pipe roller machine starting from the power source until power is used as the work cycle, and to know the type of belt, the length of the belt used on the pipe roll machine. From this research can be concluded that: (1) In bending the thickness of 4 mm pipe the required power is 582.4 N with power of 0.4 hp then the motor required 1 hp, the diameter of the pulley used is 2 inch for motoran and 8 inch for the pivot reducer, belt used type B with length 44 inch, (2) To reach the rotation of Â± 2 rpm ie pulley diameter used with the ratio of pulley ratio is 1: 4, the reducer is used with the value I = 60 and sprocket ratio 1: 3.